Innovative Approaches to Disaster Education: Integrating Problem-Based Learning with Simulated Earthquake Drills to Boost Students' Spatial Intelligence - Krisnawati Baby Kusumah; Purwanto; Rahmalia Kurnia Wardani; Julie A. Caplow (Future Space: Studies in Geo-Education, 2024)
Spatial thinking skills are essential for interpreting geographic relationships, critical for understanding spatial regions and for applications in emergency response and disaster preparedness. Given that Indonesia experiences frequent natural disasters, especially earthquakes, it is crucial to understand self-rescue strategies and disaster education. The Problem-Based Learning (PBL) model is one approach used to enhance spatial thinking abilities. The aim of this research is to examine the impact and effectiveness of the Problem-Based Learning model supported by emergency response simulations. This study is a quasi-experimental research using a quantitative approach. Data collection was conducted through a standardized final assessment specifically designed to measure spatial thinking abilities. Class selection was based on students' summative scores from prior geography lessons, ensuring baseline comparability in academic performance related to spatial skills. Classes with similar scores were chosen for the study, and the experimental and control groups were determined by a random draw. The research findings show that the use of the PBL model based on emergency response simulations has a significant impact on students' spatial thinking skills, with a significance value of 0.047. The findings also indicate that the effectiveness level of the simulation-based PBL is 69%, which is considered moderately effective. Among the spatial thinking parameters assessed, location emerged as the most significantly impacted, highlighting its critical role in disaster-oriented spatial understanding.